Computation and Analysis of Topological Co-Indices for Metal-Organic Compound - Zhao, Dongming; Muhammad, Mehwish H.; Siddiqui, Muhammad Kamran; Nasir, Muhammad; Nadeem, Muhammad Faisal; Hanif, Muhammad Farhan (Current Organic Synthesis, 2021)
A topological descriptor is a mathematical illustration of a molecular construction that relates particular physicochemical properties of primary molecular structure as well as its mathematical depiction. Topological co-indices are usually applied for quantitative structure action relationships (QSAR) and quantitative structure property relationships (QSPR). Topological co-indices are topological descriptor which consider the noncontiguous vertex set. In this study, we studyied some of the accompanied renowned topological co-indices: the 1st and 2nd Zagreb co-indices, the 1st and 2nd multiplicative Zagreb co-indices, and the F-coindex. By applying structure based examinations and deductions, we discuss the earlier stated co-indices of few synthetic atomic structures that are frequently used in clinical, synthetic, and material designing
Keywords: the second multiplicative zagreb co-index